Исследование динамики многоходовых трубчатых воздухоподогревателей - Тарасенко, Николай Алексеевич; Тарасенко, Александр Николаевич; Угольников, Сергей Викторович (НТУ "ХПИ", 2018)
Выполнен обзор существующих методик расчета динамических характеристик рекуперативных трубчатых теплообменных аппаратов. Показано, что для повышения достоверности результатов расчета тепловых характеристик процессов теплообмена воздухоподогревателей целесообразно использовать математическую модель как объекта с распределенными параметрами. На основе модификации неявного численного метода "бегущего счета", разработан метод определения показателей нестационарных процессов теплообмена трубчатых воздухоподогревателей с многоходовой схемой движения теплоносителей. Получены кривые разгона и распределения температур стенок труб трубчатых воздухоподогревателей.

A review of existing methods of calculating the dynamic characteristics of the tubular recuperative heat exchangers. It is shown that in order to increase the reliability of the results of calculating the thermal characteristics of heat exchange processes for air heaters, it is expedient to use a mathematical model as an object with distributed parameters. A mathematical model of tubular air heater with a cross flow heat transfer agent, as an object with distributed parameters for different disturbance transition. On the basis of the implicit modification of the numerical method "running account", developed a method to identify indicators of unsteady heat transfer processes tubular air heaters with crossflow heat transfer fluids. Developed a set of programs that allows you to effectively conduct multiple calculations of thermal characteristics air heaters boilers in a wide range of input parameters. The numerical experiments on a mathematical model of tubular air heater and comparing the calculated results with the experimental data of the air heater. The curves of acceleration and temperature distribution and heat transfer tube wall tubular air heaters with one-way and a complex scheme of flow. The resulting graph of the temperature distribution at steady state and dynamic tubular air heaters, which excludes them from the approximate calculation methods for cross-circuit current coolants. The list of parameters that affect the dynamic performance of the air heater and heat their effect on transient and steady-state characteristics. A set of measures to improve the design and patterns include air heaters boilers. Showed that only the use of multiple calculations exploded cross flow can fully account for the effect of uneven temperatures are at the entrance to and inside the heat exchanger.
Research dynamics of multipass tubular air heaters
Keywords: процесс теплообмена; динамические характеристики; кривая разгона; неявный метод; котельная установка; heat exchange; dynamic characteristics; overclocking curve